Dual-Output Operational Transconductance Amplifier-Based Electronically Controllable Memristance Simulator Circuit - Taskiran, Zehra Gulru Cam; Ayten, Umut Engin; Sedef, Herman (SPRINGER BIRKHAUSER, 2019)
In this paper, a new floating analog memristance simulator circuit based on dual-output operational transconductance amplifiers (DO-OTA) and passive elements is proposed. Theoretical derivations are presented which describe the circuit characteristics. DO-OTA active elements in the proposed circuit are realized with CMOS transistors, and PSPICE simulations are performed. Also workability of the circuit is tested experimentally by using commercially available integrated circuits. Theoretical derivations are validated with PSPICE simulation and experimental results. All results show that proposed simulator circuit provides frequency-dependent pinched hysteresis loop and nonvolatility feature. Exciting frequency, minimum and maximum memristance values and memristance range can be adjustable electronically with bias currents by changing the transconductances of DO-OTAs. Simulator circuit has a frequency range of 1Hz-180kHz.
Keywords: Memristor; Simulator; Operational transconductance amplifier; Electronically controllable; EMULATOR; Engineering